An Indian Enigma? Labour Market Impacts of the World's Largest Livelihoods Program - Ashwini Deshpande; Shantanu Khanna; Daksh Walia (Global Labor Organization (GLO), 2023)
We examine the labour market impacts of the largest livelihoods programs in the world, India's Deendayal Antyodaya Yojana- National Rural Livelihoods Mission (DAY-NRLM). A key aspect of this program is to mobilize rural women into self-help groups (SHGs). We combine administrative data on SHG membership across districts in India with survey micro-data on labour force and employment outcomes of rural women between 2011 and 2019. Using a generalized difference-in-differences approach, we find that SHG membership is positively associated with labor force participation and employment of rural women. We also find evidence that SHG membership is associated with a shift towards self-employment and a crowd-out of casual work among the employed. Our supplementary analysis based on large primary survey data from Maharashtra allows us to examine the relationship between SHG membership and economic activity at the individual level. This confirms our main results of a positive association between SHG membership and economic activity. Further, we show that longer duration of SHG membership is associated with higher participation rates.
Keywords: O20; O22; J16; 330; Self-Help Groups; Labor Force Participation; Employment; India